Illative Sense John Henry Newman: Relevansi dan Kekuatannya - Situmorang, Riston (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2014)
For John Henry Newman, the illative sense is a faculty owned universally and not particularly by every human being. It is an ability that converges from the various particularities into the one and the same substance, that is, the existence of God. Newman’s illative sense is a way of explaining the sensus fidelium, which is based not simply on the intellect but also on ‘the logic of the heart’. It is a potential to deduce based on the consciousness of the conscience through understanding, judgment, and senses concerning the meaning of a phenomenon. This faculty can assess and conclude in a perfect way, and is beneficial during the process of the mind in deciding naturally whether something is right or wrong within the concrete circumstances. In the light of this idea, Newman’s illative sense is regarded helpful to understand the believers’ way of apprehension in matters of faith, for they might have adopted a particular way of apprehending the objects of faith. This article tries to put the whole idea of illative sense in its relevance to the history and the development of philosophical and theological thoughts.